Bilateral lung cancer showing various responses to immune checkpoint inhibitors: A case report. Issue 5 (11th August 2020) - Kodama, Hiroaki; Ibe, Tatsuya; Inoue, Rentaro; Shimada, Tetsuya; Ishii, Hisashi; Hamamoto, Yoichiro
Abstract: Background: Combination immune checkpoint inhibitor (ICI) therapy has become the mainstay in cancer treatment, and the various antitumor effects of ICIs are being observed. Synchronous multiple primary lung cancers (SMPLCs), which simultaneously involve tumors of different histologies, are often encountered in clinical settings. In standard lung cancer treatment, an anticancer drug, usually a platinum‐based drug, is administered, and this first treatment provides some antitumor effect. Thus, the initial administration of platinum‐based anticancer agent may mask the detection of SMPLCs. The following case represents different antitumor effects on two different primary lung lesions during treatment with ICIs. Case presentation: A 72‐year‐old man was referred to our hospital for an abnormal chest shadow, and computed tomography showed masses in the left lower and right upper lungs. Transbronchial lung biopsy from the left lung tumor revealed an adenocarcinoma. Following the administration of pembrolizumab (200 mg/body over 3 weeks) as monotherapy, the tumor in the left lung rapidly reduced in size. However, the tumor in the right upper lung continued to grow. Finally, his disease was diagnosed as SMPLCs of adenocarcinoma and small cell lung cancer. Conclusion: Bilateral lung lesions considered to be intrapulmonary metastases have completely different responses to ICI treatment. It is necessary to consider a diagnosis of SMPLCs if lesions with different responses to antitumor therapy are observed.